Strategi Pembinaan Profesionalisme Da’iyah Di Pondok Pesantren Salafiyah Tahfidzul Qur’an Muhammad Natsir Putri Lampung Selatan - Purwanti, Putry Adinda; Yanti, Yunidar Cut Mutia; Mubasit, Mubasit (FDIK IAIN Padangsidimpuan, 2025)
This study examines the strategies for developing the professionalism of Da’iyah at Pondok Pesantren Salafiyah Tahfidzul Qur’an Muhammad Natsir Putri using a qualitative case study approach. The development strategies are designed to enhance three main dimensions: cognitive, psychomotor, and affective, through a series of structured, competent, and contextual activities. In the cognitive dimension, the strategy focuses on strengthening knowledge of Islamic law (Ilmu Syar’i) through an integrated curriculum that combines Quran memorization with intensive study of primary classical texts (Tafsir, Hadith, Fiqh, and Aqidah) and specialized scholarly assemblies (majlis syar’i) as forums for deepening tafaqquh fiddin. This equips Da’iyah with profound and valid understanding of religious knowledge.The strategy for the psychomotor dimension emphasizes developing oratory and digital preaching skills through regular speech practice (muhadharah) and media literacy training to effectively broaden the reach of da’wah, making it relevant to millennial audiences. Meanwhile, in the affective dimension, the development is directed toward building moral integrity through the culture of exemplary behavior (Uswatun Hasanah) and a nurturing pesantren environment that instills consistency between words and actions.Evaluations of these developmental strategies reveal improvements in Da’iyah’s competence in understanding and applying Islamic knowledge, communicating effectively, and maintaining moral credibility in preaching. Overall, these strategies successfully produce professional Da’iyah who are adaptive to social dynamics and uphold high ethical standards in line with the demands of contemporary da’wah. Penelitian ini mengkaji strategi pembinaan profesionalisme Da’iyah di Pondok Pesantren Salafiyah Tahfidzul Qur’an Muhammad Natsir Putri dengan pendekatan kualitatif studi kasus. Strategi pembinaan dirancang untuk mengembangkan tiga dimensi utama yaitu kognitif, psikomotorik, dan afektif, melalui rangkaian kegiatan terstruktur yang kompeten dan kontekstual. Pada aspek kognitif, strategi pembinaan menitikberatkan pada penguatan ilmu syar’i melalui kurikulum terintegrasi yang menggabungkan hafalan Al-Qur’an dengan kajian intensif kitab kitab induk (Tafsir, Hadits, Fiqh, Aqidah) serta majelis syar’i sebagai forum pendalaman tafaqquh fiddin untuk membekali Da’iyah dengan pemahaman ilmu agama yang mendalam dan valid.Strategi pembinaan pada dimensi psikomotorik berfokus pada pengembangan keterampilan orasi dan dakwah digital melalui praktik berpidato (muhadharah) secara rutin dan pelatihan literasi media untuk memperluas jangkauan dakwah secara efektif dan relevan dengan audiens millennial. Sedangkan pada aspek afektif, pembinaan diarahkan pada pembentukan integritas moral melalui budaya teladan Uswatun Hasanah dan keteladanan lingkungan pesantren yang menanamkan konsistensi antara ucapan dan tindakan.Evaluasi terhadap strategi pembinaan ini menunjukkan peningkatan kompetensi Da’iyah dalam memahami, mengaplikasikan ilmu syar’i, berkomunikasi secara efektif, serta menjaga kredibilitas moral dalam dakwah. Keseluruhan strategi pembinaan ini berhasil menghasilkan Da’iyah profesional yang adaptif terhadap dinamika sosial serta beretika tinggi sesuai tuntutan dakwah modern.